Pengaruh Kepercayaan, Kepuasan Konsumen dan Citra Merek Terhadap Loyalitas Konsumen Ms Glow di Kota Batam - Vira Aulia Zakna; Nur Elfi Husda (Forum Kerjasama Pendidikan Tinggi, 2025)
This research aims to analyze the influence of trust, customer satisfaction, and brand image on consumer loyalty to MS Glow in Batam City. The research uses a quantitative descriptive method because the population consists of consumers who have purchased or used Ms Glow products, with an unknown exact number. The sample size was determined using the Lemeshow formula, resulting in 100 respondents for data collection. The method used was non-probability sampling technique. (purposive sampling). The research results show that trust has an influence but is not significant on consumer loyalty, consumer satisfaction has a significant influence on consumer loyalty, and brand image has a significant influence on consumer loyalty. This research suggests that companies should focus on improving brand image and consumer satisfaction to enhance consumer loyalty.